Development of Disaster Mitigation Interactive E-Modules Based on Socio-Scientific Issues (SSI) to Facilitate Junior High School Students' Science Literacy - Nofenka Permata Islami; Agung Mulyo Setiawan (Universitas Pendidikan Mandalika, 2025)
In the 21st century, scientific literacy is crucial for students as it connects science to real-life issues. The Socio-Scientific Issues (SSI) approach can be used through contextual learning to enhance students' scientific literacy. This approach involves developing teaching materials based on SSI and for this research, the focus is on disasters and mitigation to increase preparedness in disaster-prone areas. The research aims to develop and test the feasibility and practicality of SSI-based teaching products using the Research and Development (R&D) method, specifically the ADDIE model. The novelty of the SSI e-module is in the issues discussed, the interactive and varied material, and the quiz features. These can improve students' scientific reasoning by involving them in real-life problem-based discussions relevant to everyday life, thus encouraging critical analysis, decision-making, and collaborative problem-solving.Data was collected through interviews with teachers to analyze their needs and through questionnaires distributed to students, feasibility tests, and product practicality tests. The results showed 90% material feasibility, 100% concept correctness, 95% media feasibility, and 96% question feasibility, all falling within the